2010
DOI: 10.1016/j.foodcont.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation on reduction of mycotoxins in black pepper

Abstract: a b s t r a c tGamma ray was applied to reduce mycotoxins, i.e. ochratoxin A (OTA) and aflatoxins B 1 , B 2 , G 1 and G 2 (AFB 1 , AFB 2 , AFG 1 and AFG 2 ) in black pepper. Response surface methodology (RSM) was applied to evaluate the effect of dose of gamma ray ranging from 0 to 60 kGy and mycotoxin concentration ranging from 10 to 100 ng g À1 on the mycotoxin reduction. The maximum reduction was found at 60 kGy which was 52%, 43%, 24%, 40% and 36% for OTA, AFB 1 , AFB 2 , AFG 1 and AFG 2 , respectively. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 22 publications
1
42
0
2
Order By: Relevance
“…Gamma irradiation was also reported to decrease the total aflatoxins and aflatoxin B 1 levels gradually, with increase in gamma irradiation dose from 0 to 10 kGy (Ghanem, Orfi, & Shamma, 2008;Gupta, Bajpai, Mishra, Saxena, & Singh, 2009;Kumari, et al, 2009). However, in another study a 24-43% reduction in aflatoxin contamination was observed with irradiation at 60 kGY (Jalili, Jinap, & Noranizan, 2010). Gaseos ozone was effectively used against aflatoxin B1 at 13.8 mg/L (Zorlugenc, Kiroglu Zorlugenc, Oztekin, & Evliya, 2008).…”
Section: Other Foodsmentioning
confidence: 96%
“…Gamma irradiation was also reported to decrease the total aflatoxins and aflatoxin B 1 levels gradually, with increase in gamma irradiation dose from 0 to 10 kGy (Ghanem, Orfi, & Shamma, 2008;Gupta, Bajpai, Mishra, Saxena, & Singh, 2009;Kumari, et al, 2009). However, in another study a 24-43% reduction in aflatoxin contamination was observed with irradiation at 60 kGY (Jalili, Jinap, & Noranizan, 2010). Gaseos ozone was effectively used against aflatoxin B1 at 13.8 mg/L (Zorlugenc, Kiroglu Zorlugenc, Oztekin, & Evliya, 2008).…”
Section: Other Foodsmentioning
confidence: 96%
“…Some researchers reported a significant reduction and in many cases the complete elimination of mycotoxins in various foods; (Jalili, Jinap, & Noranizan, 2010;Herzallah, Alshawabkeh, & AL Fataftah, 2008;Prado et al, 2003;Jalili, Jinap, & Noranizan, 2012); other data, instead, are in complete disagreement with these (Hooshmand & Klopenstein, 1995;Feuell, 1966). …”
Section: Twelfth Edition 2011)mentioning
confidence: 99%
“…The extrusion grits cooking caused significant reduction of FB1 in all treatments if compared with the not extruded used as control. The use of glucose resulted in a greater reduction (44.8-66.6%) compared to fructose (32.4-52.2%) or sucrose (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42).7%) use.…”
Section: Fumonisinsmentioning
confidence: 99%